AUTOMATION AND OPTIMIZATION OF XARM ROBOT CONTROL - Jalilov Mashkhurbek Islomidin ugli (European Science Publishing, 2024)
Using Python xArm such as the robot to manage automation robotics and automation point of view in terms of opportunities the world opens . Python robotics, machine learning and the computer vision for simplicity and wide libraries because of such tasks for famous programming is a languagexArm documents and with the API get to know you want With this robot how contact do , commands to send and feedback acceptance to do about information will give . xArm the manage Python code for to write to start can Robot's opportunities and sure to your goals depending on you robotics ( for example , ROS - Robot Operation system ), the car learn ( object determination or the way planning such as tasks for ) or the computer view ( eg tasks for ) libraries your installation need to be can object observation or localization ). To see the feasibility and effectiveness of automating the control of the xArm robot using the Python programming language, by developing Python code using the xArm SDK, ROS, OpenCV and other relevant libraries, accurate and efficient control of the xArm robot is achieved, which enables it to perform various tasks autonomously and with humans. made it possible to perform in cooperation. Contributes to the development of robotic automation by demonstrating Python's capabilities in developing complex control algorithms, integrating sensor data processing, and facilitating human-robot interaction. Using Python's flexibility, modularity, and broad ecosystem, researchers and engineers can accelerate the development of robotic systems and solve real-world problems in a variety of application areas.
Keywords: Python, xArm robot , xArm SDK, Machine learning, Computer vision, ROS.